Effectiveness of telerehabilitation in postoperative outcomes in patients on hip fracture surgery: a meta-analysis of randomized controlled trials - Huangyi Xiao; Wenshu Zeng; Lanmo Lu; Jiankun Yuan; Ziyu Yan; Jun Wang (BMC Sports Science, Medicine and Rehabilitation)
Abstract Objective To comprehensively assess the rehabilitation efficacy of telerehabilitation compared with other traditional rehabilitation therapies in postoperative hip fracture patients. Data sources Seven electronic databases: PubMed, Embase, The Cochrane Library, Web of Science, CNKI, Wan Fang, and VIP Databases, were searched from inception until October 2023. Study selection Two independent reviewers selected randomized controlled trials (RCTs) that assessed the efficacy of telerehabilitation intervention approach to postoperative hip fracture rehabilitation. An outcome measure related to hip function, functional independence, anxiety levels, walking ability, quality of life, and treatment adherence were eligible. Data extraction Two reviewers independently used the Cochrane Risk of Bias 2 (RoB 2) tool for risk of bias and data extraction. RevMan 5.4 and Stata 15.1 were used for statistical analysis. Data synthesis Seventeen RCTs (n = 1577) met the inclusion criteria. Compared to the usual care group, the telerehabilitation group demonstrated a noteworthy enhancement in hip function, as evidenced by the Harris Hip Score (SMD = 1.05, 95% CI (0.64, 1.45)). Significant improvements in functional independence (Functional Independence Measure: SMD = 1.38, 95% CI (1.08, 1.68)), adherence to rehabilitation treatment (Medical Compliance Behavior Scale: SMD = 1.23, 95% CI (0.71, 1.76)), and quality of life (SMD = 1.04, 95% CI (0.42, 1.65)) were also observed in the telerehabilitation group. However, no statistically significant distinction was observed in anxiety improvement (as assessed by the Self-Rating Anxiety Scale: SMD = -0.67, 95%CI (-1.65, 0.31)) or in terms of walkability (Timed Up and Go Test: SMD = -0.06, 95% CI (-0.32, 0.20)) when compared to the usual care group. This may be related to patient participation, differences in telerehabilitation interventions, and inconsistent follow-up durations among different studies. Conclusions Current evidence suggests that telerehabilitation may help improve hip function, increase functional independence, and improve treatment adherence in patients after hip fracture surgery. Nonetheless, it does not demonstrate a significant impact on reducing patients’ anxiety or improving their walking ability.